PENGETAHUAN IBU MERUPAKAN FAKTOR DOMINAN DALAM PEMBERIAN ASI EKSKLUSIF - Theresia Eugenie; Jomima Batlejeri; Meriam Napitupulu (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Exclusive breastfeeding is a program to feed the infant breast milk only from newborns tosix months age. Breast milk has benefit to improve infant immunity so that it is strongrecommended. The purpose of this study was to determine the factors associated withexclusive breastfeeding in the PHC Kec.Cengkareng West Jakarta. The methodology of thisresearch with a quantitative approach with cross sectional design. Subjects were 84 motherswith infants aged 6 months plus to 12 months who attend health centers in West JakartaKec.Cengkareng in 2014. Data collection was made through questionnaires distribution.Bivariate data was analyzed using chi-square test with ? 5%. Result: There are82.1% ofmothers in Public Health Center Kec.Cengkareng 2014 apply exclusive breastfeeding withdetermined of knowledge (p value 0.005), maternal attitude (p value 0.047), exposureinformation ( p value 0.032). Multivariate analysis using logistic regression shows that,mothers knowledge is the most dominant factor for applying exclusive breastfeeding,withOdd Ratio 5.183. Recomendation: knowledge on exclusive breastfeeding should be sharedto all women, especially mothers.